Understanding tungsten erosion during inter/intra-ELM periods in He-dominated JET-ILW plasmas. (22nd October 2021) - Huber, A; Brezinsek, S; Huber, V; Solano, E R; Sergienko, G; Borodkina, I; Aleiferis, S; Meigs, A; Tskhakaya, D; Sertoli, M; Baruzzo, M; Borodin, D; et al.
Abstract: Tungsten erosion was quantified during inter/intra-ELM periods in He-dominated JET-ILW plasmas by optical emission spectroscopy. The intra-ELM tungsten sputtering in helium plasmas, which dominates the total W source, prevails by a factor of about 4 over inter-ELM sputtering in the investigated ELM frequency range from 90 Hz–120 Hz. He ions are mainly responsible for the W erosion during the ELMs in He plasmas. The strong in/out asymmetry of the ELM-induced W erosion is observed in He plasmas even at high ELM frequencies beyond 100 Hz. In Ohmic/L-mode plasmas and during the H-mode inter-ELM plasma phases both He 2+ and Be 2+ ionic species are major contributors to the W erosion. Their contribution depends on the electron temperature in the divertor: for Te > 15 eV both species cause significant W sputtering, for Te < 15 eV, Be 2+ ions are solely responsible for the W erosion. Tungsten erosion during in both inter and intra-ELM periods in He-dominated plasmas are significantly larger than in deuterium plasmas. It is 15–25 times larger during the inter-ELM phase and in L-mode discharges at Te = 25–30 eV. On the other hand, the ELM-induced W source is by a factor of 3 larger than in D plasmas.